Chromatin and transcription - Kornberg, Roger (Henry Stewart Talks, 2007)
Chromatin remodeling for transcription, The RNA polymerase II transcription machinery, Mediator of transcriptional regulation, Atomic structure of RNA polymerase II and of a transcribing complex, Structural basis of ribonucleotide addition and transcript elongation, Structure of a complete pre-initiation complex
Archived at 2016/04/17